Little Blue Truck and Racer Red - Schertle, Alice; Joseph, John, 1985- (New York, NY : Clarion Books, an imprint of HarperCollinsPublishers, 2025)
"Little Blue Truck and good friend Toad are out for a drive when a flash of red whizzes by--then whizzes back to stop and say hi. Sleek and low, Racer Red is made for speed and loves to go fast! When she challenges Blue to a race, Blue knows that win or lose, it's fun to try! Beep! Beep! Zooooom!"--Provided by publisher.
Keywords: Trucks -- Juvenile fiction; Automobiles, Racing -- Juvenile fiction; Friendship -- Juvenile fiction; Animals -- Juvenile fiction; Trucks -- Ficton; Automobiles, Racing -- Fiction; Friendship -- Fiction; Animals -- Fiction; Stories in rhyme; Stories in rhyme; Picture books